Pengaruh Intervensi Psikoedukasi Berbasis Audio Visual Terhadap Internet Addiction - Suci Ratna Estria; Siti Nurjanah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: to determine the effect of audiovisual-based psychoeducation interventions on internet addiction.Methods: Research design was quasy experiment with control group. The sample are 51 respondents. Data was analyzed using paired t test.Results: There are differences in internet addiction scores (p value 0.0001) in both of groupsConclusion: intervention for internet addiction was effectively intervened with psychoeducation. In particular this intervention applying psychological treatments that can increase the effectiveness of intervention for internet addiction is more than just cognitive treatment. This shows that innovative intervention approaches are more effective in dealing with internet addiction